Preparation and Characterization of Ternary Antimicrobial Films of β-Cyclodextrin/Allyl Isothiocyanate/Polylactic Acid for the Enhancement of Long-Term Controlled Release - Jinpeng Wang (Materials, 2017)
Allyl isothiocyanate (AITC) are natural essential oil components that have outstanding antimicrobial activities. However, low water solubility, high volatility, and easy degradation by heat, restricting their application in food packing industry. Development of the inclusion complex of β-cyclodextrin/AITC (β-CD/AITC) is a promising solution. Furthermore, the incorporation of β-CD/AITC complex into polylactic acid (PLA) films would be an attractive method to develop food antimicrobial materials. The aim of this study was to evaluate the enhancement in physicochemical properties, antimicrobial activities, and controlled release of β-CD/AITC from such films. The addition of β-CD/AITC significantly increased the flexibility and thermal stability of films. The Fourier transform infrared (FTIR) results revealed that the interactions between β-CD/AITC and PLA films occurred. The controlled release of AITC encapsulated in β-CD was significantly affected by relative humidity and temperature. The PLA films containing β-CD/AITC can be applied as an effective antimicrobial packing material for food and non-food applications.